Innovation process tracing assessment: Methodological approach and guiding principles - Giordano, Nicola; Aston, Thomas; Wadeson, Alix Sara; Adamseged, Elias; Michalscheck, Mirja; Minh, Thai Thi (International Food Policy Research Institute, 2024)
The "Rethinking Food Markets and Value Chains for Inclusion and Sustainability” Initiative aims to provide evidence on what types of bundled innovations, incentive structures, and policies are most effective for creating more equitable sharing of income and employment opportunities in growing food markets while reducing the food sector’s environmental footprint. The Initiative targets approximately 30,000 individuals across six geographical areas, focusing on four key innovation areas: vertical coordination models, product quality certification, digital logistics, and finance innovations, along with global knowledge assessment. The approach to evaluating the initiative's impact is based on a combination of theory-based methodologies, explicitly focusing on Process Tracing (PT) for the impact evaluation phase. The evaluation is designed to reflect on the success and learnings of the initiative while strengthening CGIAR's practice of theory-based methods such as PT and integrating innovative techniques like "causal hotspots" and Outcome Harvesting for more nuanced analysis. At its core, this evaluation prioritizes and focuses on detailed case studies of selected innovation bundles. This distinctive feature allows for an in-depth analysis of significant outcomes within the initiative. The selection process is guided by the "causal hotspot" strategy for Contribution Analysis (CA) combined with Outcome Harvesting (OH), which helps identify key areas of impact prior to the PT application. The PT methodology is then rigorously applied to examine the plausibility of each innovation's contributions and the strength of supporting evidence. This provides valuable insights to scaling efforts and evidence-based decision-making.